Clinical characterisation of exacerbations of severe eosinophilic asthma occurring on mepolizumab and placebo - Howell, I; Bratton, DJ; Hynes, G; Yancey, SW; Heaney, LG; Pavord, ID; Shrimanker, R (European Respiratory Society, 2024)
Asthma exacerbations in people treated with mepolizumab result in less peak expiratory flow reduction than placebo but similar symptom scores. Symptoms recover slower, indicating these exacerbations may be less prednisolone responsive.